A 'chromogenic' and 'fluorogenic' bis-Schiff base sensor for rapid detection of hydrazine both in solution and vapour phases. Issue 24 (25th November 2015) - Ghorai, Anupam; Mondal, Jahangir; Bhattacharya, Sumantra; Patra, Goutam Kumar
Abstract : A simple, cost effective Schiff base ligand has been exploited as a fluorescent-colorimetric probe for rapid detection of hydrazine both in liquid and gas phase based on hydrogen bonding recognition. It has good practical applicability in different environmental and biological samples. Abstract : A novel, convenient and rapid method has been developed, for the first time, for visual detection of hydrazine exploiting a simple, cost-effective Schiff base ligand, L as a fluorescent–colorimetric probe. The sensing behaviour is based on hydrogen bonding recognition. The probe could selectively distinguish hydrazine with an OFF–ON fluorescence signal change and the visible colour change from yellow to colourless at room temperature within 10 seconds. It exhibits exclusive selectivity towards hydrazine over different amines, metal cations and anions. The sensitivity of the fluorescence based assay (0.1 μM or 3.2 ppb) for hydrazine is far below the TLV (threshold limit value) set by the World Health Organization (WHO) and United States Environmental Protection Agency (USEPA). DFT and TDDFT calculations were performed on the molecule ofL in order to get the structural information and to get better insight into the sensing mechanism. The probe can be successfully used for vapour-phase discrimination of hydrazine by the TLC plate technique and it shows good practical applicability in the detection of hydrazine in water and urine samples.